Educational Challenges Of Transgender - et. al., M. Gnana Kamali, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The right to choose one’s gender identity is an essential part to lead a life with dignity which again falls under the ambit of Article 21. Transgender persons are deprived of social and cultural participation and hence they have restricted access to education, health care and public places which further deprives them of the Constitutional guarantee of equality before law and equal protection of laws. It has also been noticed that the community also faces discrimination as they are not given the right to contest election, right to vote (Article 326), employment, to get licenses, etc. and in effect, they are treated as outcast and untouchable. Section-21 makes provision that all Government institutions of primary, secondary and higher education and all primary, secondary and higher education institutions receiving aid from the Government shall reserve two percent of the total seats in each class or course for transgender persons